Conventional and Indigenous Biodiversity Conservation Approach: A Comparative Study of Jachie Sacred Grove and Nkrabea Forest Reserve - Samuel Boadi; Collins Ayine Nsor; Daniel Haruna Yakubu; Emmanuel Acquah; Osei Owusu Antobre (International Journal of Forestry Research)
Conventional managed forests and sacred groves are seldom assessed to determine their effectiveness in biodiversity conservation strategies. This study investigated tree and insect diversity in Jachie sacred grove (JSG) and Nkrabea forest reserve (NFR) in Ashanti region, Ghana. The study area constituted eight plots of 50 × 50 m along two 300 m long transects. Insects were sampled in eight pitfall traps, diagonally between the transects. Out of 150 individuals, 13 species in NFR and 15 species from JSG were registered. Celtis mildbraedii was the most dominant species in NFR = 43.18% and JSG = 23.58%. Mean DBH showed a significant relationship with basal area in NFR and JSG. Tree diversity and richness were higher in JSG (H′ = 1.43–2.3 ± 0.10; D = 1.8–3.69 ± 0.30) compared to NFR (H′ = 0.86–1.56 ± 0.09; D = 1.1–2.3 ± 0.57). However, insect diversity was higher in NFR (H′ = 1.34 ± 0.10) than in JSG (H′ = 0.5 ± 0.005). Camponotus furvus and Pachycondyla tarsata were most abundant in JSG and NFR, respectively. These findings will help conservationists work closely with traditional authorities in protecting sacred groves as key biodiversity hotspots.